Examining decentralization and managerial decision making for child immunization program performance in India. (January 2023) - Feldhaus, Isabelle; Chatterjee, Susmita; Clarke-Deelder, Emma; Brenzel, Logan; Resch, Stephen; Bossert, Thomas J.
Abstract: Despite widespread adoption of decentralization reforms, the impact of decentralization on health system attributes, such as access to health services, responsiveness to population health needs, and effectiveness in affecting health outcomes, remains unclear. This study examines how decision space, institutional capacities, and accountability mechanisms of the Intensified Mission Indradhanush (IMI) in India relate to measurable performance of the immunization program. Data on decision space and its related dimensions of institutional capacity and accountability were collected by conducting structured interviews with managers based in 24 districts, 61 blocks, and 279 subcenters. Two measures by which to assess performance were selected: (1) proportion reduction in the DTP3 coverage gap (i.e., effectiveness), and (2) total IMI doses delivered per incremental USD spent on program implementation (i.e., efficiency). Descriptive statistics on decision space, institutional capacity, and accountability for IMI managers were generated. Structural equation models (SEM) were specified to detect any potential associations between decision space dimensions and performance measures. The majority of districts and blocks indicated low levels of decision space. Institutional capacity and accountability were similar across areas. Increases in decision space were associated with less progress towards closing the immunization coverage gap in the IMI context. Initiatives to support health workers and managers based on their specific contextual challenges could further improve outcomes of the program. Similar to previous studies, results revealed strong associations between each of the three decentralization dimensions. Health systems should consider the impact that management structures have on the efficiency and effectiveness of health services delivery. Future research could provide greater evidence for directionality of direct and indirect effects, interaction effects, and/or mediators of relationships. Highlights: Study found key relationships between decision space, capacity, and accountability. SEM can be used to detect linkages between decentralization and performance. Increased managerial decision space was associated with increased capacity. Increased decision space was associated with less progress closing coverage gaps. Study may support centralization of immunization services for hard-to-reach groups.